2012
DOI: 10.1038/nchembio.1105
|View full text |Cite
|
Sign up to set email alerts
|

DAGLβ inhibition perturbs a lipid network involved in macrophage inflammatory responses

Abstract: The endocannabinoid 2-arachidonoylglycerol (2-AG) is biosynthesized by diacylglycerol lipases DAGLα and DAGLβ. Chemical probes to perturb DAGLs are needed to characterize endocannabinoid function in biological processes. Here, we report a series of in vivo-active 1,2,3-triazole urea inhibitors, along with paired negative-control and activity-based probes, for the functional analysis of DAGLβ in living systems. Optimized inhibitors showed excellent selectivity for DAGLβ over other serine hydrolases, including D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
394
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(422 citation statements)
references
References 48 publications
26
394
2
Order By: Relevance
“…1A), serve as useful inactive control probes that display greatly attenuated inhibition of DAGLs, while maintaining activity against common off-targets like ABHD6 (27). Based on this precedent, we synthesized DO53 (8), a 2-phenyl piperazine analog of DO34, and found that this agent exhibited ∼100-fold lower activity against DAGLα compared with DO34 or DH376 as measured by DAG substrate hydrolysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A), serve as useful inactive control probes that display greatly attenuated inhibition of DAGLs, while maintaining activity against common off-targets like ABHD6 (27). Based on this precedent, we synthesized DO53 (8), a 2-phenyl piperazine analog of DO34, and found that this agent exhibited ∼100-fold lower activity against DAGLα compared with DO34 or DH376 as measured by DAG substrate hydrolysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The development of DAGL inhibitors has been historically hindered by a dearth of assays for monitoring the activity of these enzymes in native biological systems. We have recently introduced tailored activity-based probes that enable the independent and concurrent monitoring of DAGLα and DAGLβ activities in the brain and other tissue/cell types (27,28). Guided by competitive activitybased protein profiling (ABPP) methods (29), we converted one of these tailored probes into a series of potent 1,2,3-triazole urea (1,2,3-TU) inhibitors of DAGLβ that displayed peripheral, but not central activity in vivo (27) [e.g., KT172 (1)] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLA 2 inhibitor Wyeth-1 was produced as previously described (36). The abhydrolase domain containing 6 (ABHD6) inhibitor KT195 and BODIPY-labeled probe HT-01 used for activity based protein profiling (ABPP) assays were synthesized as previously described (37).…”
Section: Methodsmentioning
confidence: 99%
“…were treated with KT195 and pyrrophenone, followed by preparation of membrane proteomes that were probed with BODIPY-labeled HT-01 to detect ABHD6 (37). The effect of the inhibitors added directly to the proteome in vitro was also tested.…”
Section: ϫ/ϫmentioning
confidence: 99%